The importance of heritage conservation in architectural education at university level - Kirschke, Krystyna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
The subject of the article covers analyses of the methods and effects of architectural and conservation education at the university level on the basis of the research results of the Erasmus+ SURE project and our own experience in creating and implementing conservation curricula at the Faculty of Architecture of Wroclaw University of Science and Technology. The observations concerning the works sent to the Professor Jan Zachwatowicz International Competition (ICOMOS Poland), in which master's diploma projects on the protection and restoration of architectural monuments were evaluated, were presented as a comparative material. It is a place of confrontation of the effects of teaching in the majors of architecture and heritage conservation, which shows differences in systems and methods of teaching at universities. This made it possible to draw conclusions regarding education in the specialization of architecture and urban planning as well as to outline necessary program changes, some of which were successfully implemented in Poland in 2020, by introducing a new core curriculum.